Factors affecting Climate Smart Agriculture adoption - Mulila-Mitti, Joyce (Technical Centre for Agricultural and Rural Cooperation, 2019)
Joyce Mitti, a researcher and plant specialist, explains that in order to convince a farmer to adopt Climate Smart Agricultural practices, they need to understand why they have to change and why they are doing things differently.